Modelagem do sistema de avaliação de conhecimento, segundo parâmetros do ENADE, aplicável aos cursos superiores de graduação: uma proposta quanto a forma de avaliação nas IES - PEREIRA, Cléber Augusto (2010)
The proposed modeling system for assessing undergraduate degree courses, according to the parameters required by ENADE emerges from the need of the IES adjust its methodology and assessment procedures to the terms set by the exam. The proposed solution does not address a specific undergraduate course and may be applied for any knowledge area. The use of software agents is justified on the grounds of a classical computer application not being able to adapt to the reality of each student, delivering the second behavioral questions identified during the evaluation process.The statistics generated from this reasoning will serve both for students and for teachers in order to reevaluate the teaching and learning process. The modeling was performed according to the UML 2.0 TROPOS methodology was used for the modeling of agents and their implementation was done in JADE.